2020
DOI: 10.5812/aapm.99796
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Nerve Block for Rigid Bronchoscopy in the Patients with Tracheal Stenosis: A Case Serie

Abstract: Background: Rigid bronchoscopy is often used to diagnose and treat the location of resection of the tracheal stenosis. It is a selective procedure for the dilatation of tracheal stenosis, especially when accompanied by respiratory distress. Objectives: We introduced patients who were diagnosed with tracheal stenosis and candidate for rigid bronchoscopy dilatation by the upper airway nerve blocks. Methods: This prospective observational study was conducted on 17 patients who underwent dilatation with ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Also, it is suggested that video laryngoscopy in comparison to direct laryngoscopy can provide better visualiza-tion for intubation of the trachea in congenital heart disease. However, it needs time and a well-trained expert (64). In children with tongue trauma, a flexible laryngeal mask airway is more appropriate in comparison to the endotracheal tube because it reduces extubation time, recovery period, and hemodynamic changes to the airway control (65).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is suggested that video laryngoscopy in comparison to direct laryngoscopy can provide better visualiza-tion for intubation of the trachea in congenital heart disease. However, it needs time and a well-trained expert (64). In children with tongue trauma, a flexible laryngeal mask airway is more appropriate in comparison to the endotracheal tube because it reduces extubation time, recovery period, and hemodynamic changes to the airway control (65).…”
Section: Discussionmentioning
confidence: 99%
“…Airway assessments are often used, depending on the individual, job scenario, and study method. However, researchers suggested that certain factors be included in airway assessment to predict challenging endotracheal intubation, including Wilson score, BMI, neck circumference (NC) to Thyromental (TM) distance ratio, and ULBT (21)(22)(23). There are numerous tests to predict difficult intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Faster decline in arterial oxygen saturation in obese patients, along with the higher prevalence of restrictive lung disease, make such patients less tolerant for delayed intubation; therefore, safer and faster intubation plays a prominent role in airway management of these patients (27). The criteria for the possibility of difficult mask ventilation include history of snoring, obstructive sleep ap- nea, age over 55 years, male sex, beard, BMI over 30 kg/m 2 , and Mallampati 3 or more (28)(29)(30). The possibility of difficult intubation and potential airway management problems must be considered, and preparation should be made for it.…”
Section: Discussionmentioning
confidence: 99%